The burden of immune‐mediated refractoriness to platelet transfusions in myelodysplastic syndromes. Issue 10 (9th September 2020) - Cheok, Kathleen P. L.; Chhetri, Rakchha; Wee, Li Yan A.; Friel, Oisin; Pham, Anh; Salvi, Arabelle; McRae, Simon; Bardy, Peter; Singhal, Deepak; Roxby, David J.; Wood, Erica M.; Hiwase, Devendra K.
Background: Up to 65% of patients with myelodysplastic syndromes (MDS) have thrombocytopenia and require platelet (PLT) transfusion. The current standard of practice is to provide random‐ or single‐donor PLT transfusion and manage PLT refractoriness (PLT‐R) if and when it develops. This study assessed the prevalence and risk factors for immune‐mediated PLT‐R in patients in the South Australian (SA) MDS Registry. Study Design and Methods: A retrospective analysis of MDS patients enrolled in the SA‐MDS registry was performed. HLA data was analyzed from January 2003 to 30 June 2017 to ensure minimum follow‐up of 2 years. Results: During the study period, 341 of 681 (50%) MDS patients required at least one PLT transfusion, with 29 of 341 (9%) of all PLT transfusion patients requiring HLA‐matched PLT transfusion for PLT‐R. Of these 29 patients, 70% were females treated with disease‐modifying therapies suggesting that these patients are at high risk of HLA alloimmunization. Conclusions: Immune‐mediated PLT‐R is common in MDS and can be expensive and difficult to manage once it occurs. Therefore, PLT transfusion practices should be optimized, especially for female MDS patients planned for disease‐modifying therapies. This can help save time and streamline management, especially in the provision of PLT products for these patients, where the consequences of alloimmunization and PLT‐R can be severe. Abstract : See editorial on page 2164–2167,  in this issue